2008
DOI: 10.4067/s0718-50732008000100003
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impacts of implementing lean construction

Abstract: Assessing the impacts of implementing lean construction Evaluando los impactos de la implementación de lean construction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 3 publications
3
62
0
6
Order By: Relevance
“…Once the constraints for a task have been removed, the task is "made ready" and the commitment to accomplish the task is more reliable (González et al 2010). Look-aheads are an important aspect of the LPS® and Alarcón et al (2005) found that PPC improved when companies included the use of look-aheads while implementing the LPS®. The project manager involved with this case study stated they did not work to identify and remove constraints to the extent they had envisioned during their look-aheads.…”
Section: Methodsmentioning
confidence: 99%
“…Once the constraints for a task have been removed, the task is "made ready" and the commitment to accomplish the task is more reliable (González et al 2010). Look-aheads are an important aspect of the LPS® and Alarcón et al (2005) found that PPC improved when companies included the use of look-aheads while implementing the LPS®. The project manager involved with this case study stated they did not work to identify and remove constraints to the extent they had envisioned during their look-aheads.…”
Section: Methodsmentioning
confidence: 99%
“…Some of these studies concentrated on identifying factors that are effective in the implementation of lean construction (Abdullah et al, 2009;Oladiran, 2008) while others focused on investigating the factors that are active during the execution of lean construction (Alarcón et al, 2002;Johansen and Porter, 2003). Other researches have classified lean barriers into different categories wherein some of these studies concentrated on structural and cultural aspect (Samari et al, 2013; Sarhan and Fox, 2013) or management and strategy aspect (Ayarkwa et al, 2012;Bashir et al, 2010) or barriers that exist during the implementation of lean construction practices (Alarcón et al, 2005;Ansell et al, 2007). Bashir et al (2015) presented ten challenges related to management, technical, human, and educational issues when organizations are applying lean process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Last Planner system implemented by GEPUC resulted in a more reliable flow and a higher throughput of the production system. Increases in productivity between 7 and 48% have been reported in GEPUC Projects (Alarcón et al 2005).…”
Section: Introductionmentioning
confidence: 97%